Uji Performa Alat Vakum Tekan Termodifikasi Untuk Impregnasi Kayu - Esti Prihatini; Rohmat Ismail; Istie Sekartining Rahayu; Rizky Ramdhani (UPT Laboratorium Terpadu, Universitas Diponegoro, 2023)
The impregnation process is carried out to increase the resistance of wood from the attack of microorganisms such as fungi and termite attacks by placing the wood in a vacuum tube and then placing an impregnan solution into it. The limited ability of impregnation tubes is an obstacle in carrying out research and practicum activities, therefore there needs to be modifications to the impregnation tube so that the impregnation process can provide better results. Verification of the results of impregnation is done by calculating the value of weight percent gain (WPG) and relative standard deviation (%RSD) for the test of the level of appreciation. Based on the results of the experiment the highest %WPG value in the water impregnan solution was obtained from the parameter conditions of the type 3 press vacuum tool, which is with a time of 1 hour and a pressure of 5 bars and is worth (178.29Â±10.97). The highest %WPG value in boron solution of 5% is obtained from the condition of the type 6 press vacuum tool with a time of 3 hours and a pressure of 5 bars and is worth (5.16Â±0.45). The smallest %RSD value of water impregnan solution is achieved under the parameter conditions of type 4 tools at 3 hours and pressure 1 bar and is worth 3.99%. The smallest %RSD value of boron impregnan solution is 5% achieved under the parameter conditions of type 2 tools, namely within 1 hour and pressure of 3 bars and is worth 5.36%.